2019
DOI: 10.1016/j.csbj.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3 on the Road to Longevity: Lessons From SNPs and Chromatin Hubs

Abstract: Health span is driven by a precise interplay between genes and the environment. Cell response to environmental cues is mediated by signaling cascades and genetic variants that affect gene expression by regulating chromatin plasticity. Indeed, they can promote the interaction of promoters with regulatory elements by forming active chromatin hubs. FOXO3 encodes a transcription factor with a strong impact on aging and age-related phenotypes, as it regulates stress response, therefore affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 116 publications
0
32
0
1
Order By: Relevance
“…However, colocalisation of gene expression could be due to pleiotropy rather than causality, and there is a need to validate the effects of genetic variants in experimental models to confirm their role in disease aetiology. For example, we have found life-extending variants colocalise with decreased expression of FOXO3 in blood, which itself becomes increasingly expressed with increasing age, but experiments suggest the gene has many protective functions including detoxification of reactive oxygen species and DNA damage repair 15 . The observed inverse relationship between healthy life and FOXO3 expression may reflect healthy individuals have less oxidative damage and require less FOXO3 to mitigate this damage.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, colocalisation of gene expression could be due to pleiotropy rather than causality, and there is a need to validate the effects of genetic variants in experimental models to confirm their role in disease aetiology. For example, we have found life-extending variants colocalise with decreased expression of FOXO3 in blood, which itself becomes increasingly expressed with increasing age, but experiments suggest the gene has many protective functions including detoxification of reactive oxygen species and DNA damage repair 15 . The observed inverse relationship between healthy life and FOXO3 expression may reflect healthy individuals have less oxidative damage and require less FOXO3 to mitigate this damage.…”
Section: Discussionmentioning
confidence: 94%
“…Ten regions are of particular interest as they associate with all three ageing traits and are as such likely candidates to capture intrinsic ageing processes, rather than extrinsic sources of ageing. Five of the loci of interest are not associated at a genome-wide significant level in any individual dataset, including the region near FOXO3, which has thus far only been highlighted in candidate gene association studies (reviewed in Sanese et al 15 ) and never at genome-wide significance. The effects of loci of interest on male and female lifespan are largely the same, although their effect on survival may be slightly stronger in middle age (40-60 years) compared to old age (>80 years).…”
Section: Discussionmentioning
confidence: 99%
“…The results further demonstrated that the mRNA expression of FOXO3 was elevated in patients with mild to moderate LOA, whereas decreased in patients with severe LOA. FOXO3 had a pivotal role in inhibiting apoptosis, resisting oxidation, extending cell lifespan and preventing against aging-related diseases [ 54 ]. The increased FOXO3 expression may be due to the trigger of protective self-defense mechanisms in mild and moderate LOA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of the Pten gene was found to delay the process of proteostatis and therefore resulted in a decrease in the loss of muscle strength during muscle aging, increasing maximum lifespan in Drosophila by up to 7.7% in comparison with matched controls [50]. Interestingly, the human PTEN (phosphatase and tensin homolog) gene was found to encode upstream regulators for the FOXO3 gene [51], one of the few loci robustly associated with longevity in humans [10], stressing that longevity-associated SNPs may reside in regulatory regions as well as in protein-coding genes [52]. The Drosophila ortholog of the FOXO3 gene, foxo , a transcription factor involved in the regulation of the insulin signaling pathway, is a commonly known longevity gene [5356].…”
Section: Resultsmentioning
confidence: 99%